History of Zomi - Gougin, T. (Churachandpur, Manipur : T. Gougin, 1984)
On a Tibeto-Burman group of people comprising Lusheis, Kukis, and Chins tribes, chiefly from Mizoram, Bangladesh, and Burma.
Master microform held by: DLC.
Bibliography: p. [247]-[248]
Microfiche.
Keywords: Zomi -- History